Trust and Trustworthiness in a Sequential Bargaining Game - Ananish Chaudhuri; Sarah Ali Khan; Aishwarya Lakshmiratan; Anne-Laure Py; Lisa Shah (Wellesley College, Department of Economics, 2002)
We use a two-person extensive form bargaining game to examine individuals? trusting and reciprocal behavior and how those relate to their scores on a trust survey. In keeping with prior research, we find that the ?self-interested? outcome is rejected by a majority of individuals. People who score high on the trust survey are both trusting and are also trustworthy, in that they reciprocate others? trust. But, people with low trust scores often exhibit trust but are not trustworthy. These ?inconsistent trusters? seem to be interested in exploiting the trust and trustworthiness of others in increasing their own payoff.
Keywords: C91; C72; 330; Trust; Reciprocity; Social Values Orientation; Sequential Game; Bargaining; Vertrauen; Verhandlungen; Spieltheorie